Correspondence between the Terms and Defnitions of the International Standard ISO 21043-1-2018 and Terminology Developed by National Forensic Expertology - E. V. Chesnokova (Теория и практика судебной экспертизы, 2019)
The issue of developing a uniform language for international communication in the feld of forensic science is considered. The matters of relative maturity of domestic forensic expert terminology and peculiarities of translated terms usage in forensic expertology and forensic practice are discussed. The concept of expertise subject formulated by modern leading scientists is analyzed, the conclusion is made about the subject of forensic examination as a process of establishing facts and circumstances, the purely applied nature of the concept, as well as the similarity to the defnition of expertise in the ISO international standard. Specifc examples are given. The need to translate some foreign standards into Russian and to adjust and implement several of their provisions in domestic legal system and expert practice to standardize forensic and expert activity is emphasized.